2001
DOI: 10.1089/109065701753145583
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Hemochromatosis, a Celtic Disease: Is It Now Time for Population Screening?

Abstract: In populations of northern European ancestry, hereditary hemochromatosis (HH) is tightly linked to mutations within the hemochromatosis gene (HFE gene). Over 93% of Irish HH patients are homozygous for the HFE gene C282Y mutation, providing a reliable diagnostic marker of the disease in this population. However, the prevalence of the C282Y mutation and that of the second HFE gene mutation, H63D, have yet to be determined within the Irish population. The objective of this study was to identify the true prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 26 publications
(27 reference statements)
7
46
1
1
Order By: Relevance
“…13,38,[62][63][64][65][66][67] Six studies were prospective cohort studies, 38,62,63,[65][66][67] with two including a control group. 38,62 The other two studies were a retrospective cohort study 13 and a cross-sectional case-control study.…”
Section: Uk Epidemiology Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…13,38,[62][63][64][65][66][67] Six studies were prospective cohort studies, 38,62,63,[65][66][67] with two including a control group. 38,62 The other two studies were a retrospective cohort study 13 and a cross-sectional case-control study.…”
Section: Uk Epidemiology Studiesmentioning
confidence: 99%
“…38,62 The other two studies were a retrospective cohort study 13 and a cross-sectional case-control study. 64 The participants in the studies varied depending upon the rationale for the study, including people diagnosed with haemochromatosis, 13,38,62 people attending a blood donation service, 65,67 those on registers of newborn children 63 or heart attack sufferers, 64 and those attending for routine blood screening. 66 Control groups included healthy blood donors, 38 people registered with general practitioners 64 and people on bone marrow registers.…”
Section: Uk Epidemiology Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is approximately 10% in subjects of Celtic descent, whereas the prevalence is much lower in subjects from southern Europe. 105,106 Patients heterozygous for C282Y mutation show normal or only slightly elevated hepatic iron content and do not spontaneously develop liver injury. 107 However, these patients could theoretically be more susceptible to the development of liver disease when exposed to agents such as hepatitis viruses.…”
Section: A Case In Point: Role Of Hfe C282y Heterozygosity In Hcv-indmentioning
confidence: 99%
“…2 Although populationbased HFE screening may be a justifiable way to identify individuals at risk, it is important to evaluate screening risks and benefits, including the impact of an HFE screening program on psychosocial status or quality of life. 3,4 Previous studies examining acceptability of genetic testing for hemochromatosis note HFE genotyping is acceptable to many 5 or even most 6 individuals offered testing, and studies have not shown deleterious psychosocial outcomes. [7][8][9] This has led to a preliminary conclusion that population-based screening should not be discouraged on the basis of potential adverse psychosocial effects.…”
mentioning
confidence: 99%